Analisis Profil Kemandirian Belajar Matematika Mahasiswa Teknik Informatika Menggunakan Algoritma K-Means Clustering - Febrinita, Filda; Zaman, Wahid Ibnu; Puspitasari, Wahyu Dwi; Fanderella, Nur Cindy Intan (Universitas PGRI Semarang, 2026)
Student dependence on lecturers in mathematics learning demonstrates a low level of independence, which in turn influences learning outcomes. This study aims to group students by the level of self-regulated learning in mathematics and to describe the characteristics of each group. The study used a quantitative descriptive exploratory design. Data were collected through questionnaires and analyzed using the k-means clustering algorithm and descriptive statistics. The results showed that 18.80% of students were in the low category, with responsibility indicators 78.66%, discipline 54.75%, self-control 80.31%, initiative 56.15%, motivation 73.00%, and self-confidence 67.29%. A total of 53.85% of students were in the medium category, with responsibility indicators 87.89%, discipline 63.94%, self-control 86.30%, initiative 69.95%, motivation 86.03%, and self-confidence 81.80%. Furthermore, 27.35% of students are in the high category with responsibility indicators 97.27%, discipline 82.55%, self-control 97.42%, initiative 87.27%, motivation 97.45%, and self-confidence 95.00%. Based on these results, it can be concluded that the level of student independence in learning mathematics is dominated by the medium category. Students in the high self-regulated learning category have very good abilities in the indicators of responsibility, self-control, motivation, and self-confidence. Meanwhile, in the medium and low categories, the indicators that need improvement are discipline, initiative, and self-confidence.